Bullying Dan Hate Speech Pada Mahasiswa MPI - Fazli Abdillah; Aqilla Syafah Marwah Pohan; Eka Susanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The increasing number of cases of bullying and hate speech from year to year means that this case can be called one of the social problems in Indonesia. This is because bullying behavior and hate speech have many negative impacts on all parties involved, especially the victims. This research aims to look at the phenomenon of cyberbullying and hate speech among MPI students. Various research results show that the impact of bullying felt by victims can hinder various aspects of the development of teenagers who are targets of bullying. The research approach used is qualitative research with a focus on analyzing students in the MPI environment. The research results show that bullying can have a serious impact on MPI students, namely disrupting the learning process, reducing learning motivation, damaging mental well-being, and affecting the quality of their academic experience. Therefore, an anti-bullying program is needed that involves cooperation between students, academic staff and the authorities in creating a supportive environment so that victims feel comfortable seeking help from their environment.